Kebutuhan Informasi Pemustaka Terhadap Koleksi Perpustakaan Di Perpustakaan Dan Kearsipan Kota Sawahlunto - Dj, Ady Thio; Marlini, Marlini (Scinary, 2023)
This research aims to describe the relationship between library information needs and library collections in the Sawahlunto City Library and Archives Service. This research is quantitative research with a descriptive approach. Sampling was carried out using the random sampling method. Data collection was carried out by distributing questionnaires to respondents directly, namely users at the Sawahlunto City Library and Archives Service. The statistical methods used are editing and tabulation. The validity test uses the Pearson Product Moment formula and the reliability test uses the Cronbach Alpha formula. The research results show that the information needs of users have a significant relationship, although there is still influence from other factors.